Size and carbon acquisition in lizards from Amazonian savanna: Evidence from isotope analysis - Magnussoni, William E.; Lima, Albertina Pimental; Faria, Allessandra Saraiva; Victória, Reynaldo Luiz; Martinelli, Luiz Antônio (Ecology, 2001)
We studied the effects of lizard size, and availability of C3 and C4 plants, on stable carbon-isotope (δ13C) ratios of lizards in an Amazonian savanna. Availability of C3 and C4 plants was estimated from 500-point quadrats in each of 38 plots of 3.75 ha. Ratios of δ13C in muscle tissue were used to estimate the contributions of C3- and C4-based food chains to the diets of four species of lizards: Cnemidophorus lemniscatus, Kentropyx striata, Ameiva ameiva, and Anolis auratus. The relative contributions of C3 and C4 plants to the diets of the lizards were affected by the extent of shrub cover in C. lemniscatus, A. auratus, and possibly in K. striata. However, there was a strong effect of lizard size among and within lizard species. These results are at variance with a previous evaluation of diet overlap among size classes of these species that was based on overlap in prey taxonomic categories. This indicates that species and/or size classes of predators on arthropods may obtain their energy from food chains based on different autotrophic sources, despite high overlap in the taxonomic categories of prey.
Keywords: C3 Plant; C4 Plant; Carbon; Isotopic Analysis; Lizard